Antifungal activity of essential oils from Cinnamomum cassia, Myristica fragrans and Syzygium aromaticum against Rhodotorula mucilaginosa - Butzge, Juliana Caroline; Ferrão, Simone Krause; Mezzomo, Letícia; Calil, Luciane Noal; Mezzari, Adelina; Limberger, Renata Pereira; Apel, Miriam Anders (Drug Analytical Research, 2026)
Rhodotorula genus comprises yeasts from Sporidiobolaceae family. Considered as non-pathogenic until the last two decades, different species of Rhodotorula are emerging as pathogens in humans, with R. mucilaginosa being the most commonly involved in infections, ranging from simpler clinical conditions such as skin manifestations to more severe cases such as meningitis and endocarditis. The major facilitating agents for the emergence of these infections are invasive procedures such as catheter implants. The primary drugs of choice used to treat these infections are amphotericin B and fluconazole. However, some strains of this yeast show different degrees of resistance to these substances, thus justifying the search for new therapeutic agents. Considering this, the present study aims the investigation of the antifungal activity of the essential oils of Cinnamomum cassia (cinnamon), Syzygium aromaticum (clove) and Myristica fragrans (nutmeg) against clinical isolates of R. mucilaginosa. The essential oils were obtained by hydrodistillation and characterized by GC-MS. The investigation of the antifungal action activity was performed by the agar disc-diffusion test followed by the Minimum Inhibitory Concentration (MIC) determination. All the essential oils were species present their oil characterized by the presence of phenylpropanoids, with eugenol (77.6 to 94.4%) as the main compound of clove and E-cinnamaldehyde (90.4 to 100%) of cinnamon. Nutmeg oil is characterized by the presence of showed as main compounds the myristicin (1.8 a 12.8%) and elemicin (4.3 a 11.1%) phenylpropanoids, besides sabinene (28.2 to 44.4%) and terpinen-4-ol (16.0 to 19.5%) monoterpenes. In the investigation of antifungal activity, all the oils showed potential action against clinical isolates of R. mucilaginosa, with MICs ranging from 8 to 500 µg/mL. The results demonstrate that these oils are promising candidates in the search for new anti-Rhodotorula agents, enabling the treatment of aforementioned infections.